2009
DOI: 10.1017/s0007114509991449
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of fat deposition from non-starch polysaccharides, starch and unsaturated fat in pigs

Abstract: The aim was to evaluate under protein-limiting conditions the effect of different supplemental energy sources: fermentable NSP (fNSP), digestible starch (dStarch) and digestible unsaturated fat (dUFA), on marginal efficiency of fat deposition and distribution. A further aim was to determine whether the extra fat deposition from different energy sources, and its distribution in the body, depends on feeding level. A total of fifty-eight individually housed pigs (48 (SD 4) kg) were used in a 3 £ 2 factorial desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
1
5
0
4
Order By: Relevance
“…The results of the meat percentage analysis corroborated the findings of Halas et al (2010) and Duran-Montgé et al (2008), who demonstrated the possibility of supplementing different lipid sources into pig feed without negative consequences for these parameters, but contradicted those of Kouba and Mourot (1998) and Realini et al (2010), who indicated that ingredients with higher linoleic acid levels (plant-based oils compared with pig lard) increase muscle fat deposition.…”
Section: Resultssupporting
confidence: 67%
“…The results of the meat percentage analysis corroborated the findings of Halas et al (2010) and Duran-Montgé et al (2008), who demonstrated the possibility of supplementing different lipid sources into pig feed without negative consequences for these parameters, but contradicted those of Kouba and Mourot (1998) and Realini et al (2010), who indicated that ingredients with higher linoleic acid levels (plant-based oils compared with pig lard) increase muscle fat deposition.…”
Section: Resultssupporting
confidence: 67%
“…A melhora na eficiência de utilização do alimento nos animais submetidos aos níveis sequenciais de 1,1-1,0-0,9% de lisina digestível pode ser um indicativo de que ocorreu variação na composição do ganho, com aumento na deposição de proteína e redução na de gordura. Esta proposição também pode ser justificada pelo fato de que a deposição de tecido proteico, por agregar maior quantidade de água (1:3,4) em relação à deposição de lipídios na carcaça (Halas et al, 2010), melhora a eficiência de utilização do alimento para ganho de peso dos suínos.…”
Section: Resultsunclassified
“…Essa hipótese é confirmada em estudo realizado por LATORRE et al (2008), em que constataram correlação alta e positiva entre ganho diário em proteína e conversão alimentar, indicando que suínos com alta taxa de ganho de tecido protéico apresentam melhor eficiência alimentar. Além disso, essa proposição também pode ser justificada pelo fato de que a deposição de tecido protéico agrega mais moléculas de água (1:3,4), em relação à deposição de lipídios na carcaça (HALAS et al, 2010), resultando na melhora tanto do ganho em peso quanto da eficiência alimentar.…”
Section: Resultsunclassified